PHONETIC COMPOSITION OF RUSSIAN, UZBEK AND KHOREZMIAN LANGUAGES - Karimova , Adolat Ibragimovna; Muratova, Elvira Raisovna (Innovative Development in Educational Activities, 2023)
This article provides information about the phonetic composition of three languages: Russian, Uzbek literary and Khorezmian languages.